A baleen whale from the Pliocene of Nicaragua - Lucas, Spencer G. (2008)
An incomplete fossil skeleton of a cetacean from San Rafael del Sur in southern Nicaragua consists of 14 vertebral centra, one humerus and 10 incomplete ribs. This fossil is from the Lower Pliocene El Salto Formation and it can be identified as a balaenopterid mysticete. This is the first cetacean fossil documented from Central America and is a rare occurrence of a mysticete whale in Neogene strata of the tropical latitudes.